The Effect of Emotional Intelligence, Self-Confidence and Learning Behaviour on the Level of Accounting Understanding - Silvia Mulianingsih; Harsi Romli; Rafika Sari (ProBisnis : Jurnal Manajemen, 2023)
This study aims to analyze and describe the influence of emotional intelligence, self-confidence and learning behavior on the level of understanding of accounting. The data collection method in the study was carried out by survey method using primary data obtained through questionnaires or questionnaires. The population in this study were accounting students at Indo Global Mandiri Palembang University, class of 2018 to class of 2020. The number of samples taken in this study were 70 students. Samples were taken and in determining the size or number of samples needed in this study using the slovin formula. Emotional Intelligence, Self-Confidence and Learning Behavior as independent variables and Level of Understanding of Accounting as the dependent variable. The data analysis technique used is descriptive statistical analysis. The results of the research that has been done show that: (1) There is no significant effect between emotional intelligence variables on the level of understanding of accounting. (2) There is a significant influence between the variables of self-confidence on the level of understanding of accounting. (3) There is no significant effect between learning behavior variables on the level of understanding of accounting. (4) There is a simultaneous influence between the variables of emotional intelligence, self-confidence and learning behavior on the level of understanding of accounting